A construção da imagem social de Marjane Satrapi na graphic novel Persépolis via referenciação e atos de fala de (des)cortesia - Figueira, Mayra Duarte (2018)
Relationships between interlocutors essentially constitute a demonstration and a threat to the face of locutors and utterers. For this reason, during enunciations individuals normally intend to, via different speech acts and politeness strategies, avoid conflicts in order not to deconstruct neither their own nor others’ faces. This is due to a tacit agreement socially established in order to promote harmonic social interaction. However, there are situations in which intentional linguistic behaviors that break with the principle of harmony, with the purpose of informing speech acts such as distaste and insurgency. Moreover, in different sociointeractional contexts, the choice and the expansion of an object of discourse can sign out, case by case, acts of courtesy and discourtesy, and build, thus, a face for subjects. Faced with these arguments, this dissertation aims to scrutinize linguistic and non-linguistic performance of author surrogate Marjane, central character of Persepolis, a graphic novel fully edited in 2007. Its main hypothesis is that the main character deploys (dis)courtesy acts, that contribute to the representation of faces in social constructs. Among them, performative acts that reveal themselves to be a way to materialize an action announced by the character Marjane and, thus, to construct a representation of her face. Therefore, this character’s linguistic behavior will be analyzed stemming from the interface of Pragmatics and Textual Linguistics. Pragmatic studies will be approached based on Goffman (1975), regarding the construction of a social image, Brown e Levinson (1987), regarding politeness strategies and the construction of faces and Austin (1990) regarding speech acts. Also, we will base ourselves in Koch (2001, 2008, 2011, 2012, 2015), Cavalcante (2009, 2011) e Mondada e Dubois (2003), regarding studies on reference, categorization, and recategorization. Additionally, we will bring upon the studies of Cavalcante e Custódio Filho (2010), Ramos (2012) e Lins e Capistrano Jr. (2014) about reference and multimodality. In respect of this textual genre, we will base ourselves on the work of Ramos (2009) e Ramos e Figueira (2011).